2007
DOI: 10.1093/ageing/afl174
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled therapy in elderly COPD patients; time for re-evaluation?

Abstract: elderly patients with COPD, even when in a stable clinical condition, may be unable to gain optimum benefit from their inhaler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 24 publications
2
99
2
5
Order By: Relevance
“…Advanced age may also independently affect lung function and predict the ability to generate the peak inspiratory flow (PIF) rate required for optimal outcomes from certain DPIs, particularly the Turbuhaler, potentially affecting the type of error made [36,37]. As many as 75% of older adults may be unable to generate the minimum recommended PIF of 30 L·min −1 for a clinical response from the Turbuhaler [36], potentially leading to an inferior clinical response [38].…”
Section: Results Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced age may also independently affect lung function and predict the ability to generate the peak inspiratory flow (PIF) rate required for optimal outcomes from certain DPIs, particularly the Turbuhaler, potentially affecting the type of error made [36,37]. As many as 75% of older adults may be unable to generate the minimum recommended PIF of 30 L·min −1 for a clinical response from the Turbuhaler [36], potentially leading to an inferior clinical response [38].…”
Section: Results Validitymentioning
confidence: 99%
“…As many as 75% of older adults may be unable to generate the minimum recommended PIF of 30 L·min −1 for a clinical response from the Turbuhaler [36], potentially leading to an inferior clinical response [38]. This may be difficult to rectify in practice, with changes subsequent to counselling considered too minor to be cost-effective [39].…”
Section: Results Validitymentioning
confidence: 99%
“…85 The patient's age and ability to complete the required steps for inhalation are important factors in the process of choosing the right device. 86,87 Practitioners have to be cognizant of pediatric and geriatric populations and patients with physical and mental disabilities.…”
Section: Challenge Of Matching Patient Drug and Devicementioning
confidence: 99%
“…A study [74] specifically aimed at assessing the inhalation technique by objectively measuring the ability to generate adequate peak inspiratory flow (PIF) for a variety of inhalers demonstrated that elderly patients with COPD, even when in stable clinical conditions, were generally unable to generate sufficient inspiratory flows for the activation of the dry powder inhaler. Moreover, as the effect of age on PIF reduction was independent of the disease severity [74], it is possible to hypothesize that elderly patients with asthma may also experience similar problems.…”
Section: Practical Considerations For Elderly Patients On Long-term Dmentioning
confidence: 99%